Multi-objective optimization design of air distribution of grate cooler by entropy generation minimization and genetic algorithm. (5th September 2016) - Shao, Wei; Cui, Zheng; Cheng, Lin
Highlights: A multi-objective optimization model of air distribution of grate cooler by genetic algorithm is proposed. Pareto Front is obtained and validated by comparing with operating data. Optimal schemes are compared and selected by engineering background. Total power consumption after optimization decreases 61.10%. Thickness of clinker on three grate plates is thinner. Abstract: The cooling air distributions of grate cooler exercise a great influence on the clinker cooling efficiency and power consumption of cooling fans. A multi-objective optimization model of air distributions of grate cooler with cross-flow heat exchanger analogy is proposed in this paper. Firstly, thermodynamic and flow models of clinker cooling process is carried out. Then based on entropy generation minimization analysis, modified entropy generation numbers caused by heat transfer and pressure drop are chosen as objective functions respectively which optimized by genetic algorithm. The design variables are superficial velocities of air chambers and thicknesses of clinker layers on different grate plates. A set of Pareto optimal solutions which two objectives are optimized simultaneously is achieved. Scattered distributions of design variables resulting in the conflict between two objectives are brought out. The final optimal air distribution and thicknesses of clinker layers are selected from the Pareto optimal solutions based on power consumption of cooling fans minimization and validated by measurements. Compared with actual operating scheme, the total air volumes of optimized schemes decrease 2.4%, total power consumption of cooling fans decreases 61.1% and the outlet temperature of clinker decreases 122.9 °C which shows a remarkable energy-saving effect on energy consumption.